2010
DOI: 10.1021/jf904179m
|View full text |Cite
|
Sign up to set email alerts
|

Protein Molecular Structures and Protein Fraction Profiles of New Coproducts from BioEthanol Production: A Novel Approach

Abstract: The objectives of this study were to determine the protein molecular structures of the new coproducts from bioethanol production, quantify protein structure amide I to II and alpha-helix to beta-sheet spectral peak intensity ratio, and illustrate multivariate molecular spectral analyses as a novel research tool for rapid characterization of protein molecular structures in bioethonal bioproducts. The study demonstrated that the grains had a significantly higher ratio of alpha-helix to beta-sheet in the protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 21 publications
5
36
1
Order By: Relevance
“…The results [16,35] showed that the protein structure a-helix to b-sheet ratio was significantly different between the grains and the new co-products of bio-ethanol production. The a-helix to b-sheet ratio was significantly higher in the grains than in the co-products (1.38 versus 1.03).…”
Section: Application IIImentioning
confidence: 99%
“…The results [16,35] showed that the protein structure a-helix to b-sheet ratio was significantly different between the grains and the new co-products of bio-ethanol production. The a-helix to b-sheet ratio was significantly higher in the grains than in the co-products (1.38 versus 1.03).…”
Section: Application IIImentioning
confidence: 99%
“…40,41 The hypotheses of this study were that bioethanol processing changed the molecular structure of the proteins in DDGS as compared with the original cereal grain and that these changes in protein could be detected by a molecular spectroscopy techniqueDRIFTas has been previously reported in other cereal. 39,41 In addition, bioethanol processing changes the nutrient content and protein digestive characteristics of triticale DDGS relative to that of triticale grain…”
Section: ■ Introductionmentioning
confidence: 99%
“…The detailed descriptions were reported previously. 28,33,39 DRIFT Molecular Spectroscopy Data Collection and Analysis. DRIFT molecular spectroscopy was performed using a Bio-Rad FTS-40 with a ceramic infrared source and a mercury cadmium telluride detector (Bio-Rad Laboratories, Hercules, CA) at the Saskatchewan Structural Sciences Center (SSSC, Saskatoon, SK).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yu et al [18] reported that the grain had higher ratio of protein amide I to II in the protein structure than its distiller grain produced from bioethanol processing (grain vs. distiller grain; 4.58 vs. 2.84). Protein vibration of amide I and II depends on the protein secondary structure of the backbone and is therefore most commonly used for secondary-structure analysis [19].…”
Section: Protein Valuementioning
confidence: 99%